Sirex woodwasp Sirex noctilio (Hymenoptera: Siricidae): revisiting some past perceptions. Issue 2 (23rd June 2016) - Nahrung, Helen F.
Abstract: The Sirex Woodwasp, Sirex noctilio Fabricius, is the focus of extensive global research because of its pest status, damage potential and ongoing spread within commercial softwood plantations and native forest ecosystems worldwide. In this overview, some small but persistent errors in the reported biological attributes of S. noctilio and its biological control nematode are highlighted. First, an error is noted in the equations reported for estimating size/fecundity relationships, whereby the female S. noctilio prothorax should be measured in cm, not mm. Second, the temperature requirements for egg‐adult development time are recalculated to provide more precise estimates of lower thermal threshold (5.1 °C) and cumulative day‐degree requirements (1973) using modern software techniques. Third, the origin of the Australian laboratory culture of Amylostereum areolatum used in rearing Deladenus siricidicola is clarified: it was collected from S. noctilio in Mt Gambier, South Australia, around 1995. It is envisaged that these corrections will result in improved research efforts.